The impact of the Reformation on the formation of mentality and the moral landscape in the Nordic countries - Veikko Anttonen (Finnish Society for the Study of Religion, 2022)
Along with the Lutheran world the Nordic countries celebrated the five hundredth anniversary of the Reformation on 31st October 2017. In this article I shall examine the impact of Luther’s reform on the
formation of mentality and the moral landscape in the Nordic countries. Special reference is made to the impact of Lutheranism on the indigenous Sámi culture, a topic which has been explored extensively by Håkan Rydving, the expert in Sámi language and religion.